2019
DOI: 10.1042/cs20190924
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of CD11c+ dendritic cells in apolipoprotein E-deficient mice limits angiotensin II-induced abdominal aortic aneurysm formation and growth

Abstract: Objective: The role of chronic inflammation in abdominal aortic aneurysm (AAA) is controversial. CD11c+ antigen-presenting cells (APCs) (dendritic cells (DCs)) have been reported in human AAA samples but their role is unclear. The effect of conditional depletion of CD11c+ cells on experimental AAA was investigated in the angiotensin II (AngII)-infused apolipoprotein E-deficient (ApoE–/–) mouse model. Approach: CD11c-diphtheria toxin (DT or D.tox) receptor (DTR), ovalbumin (OVA) fragment aa 140–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Vascular inflammatory reactions seem to play a pivotal role in the development and progression of aortic aneurysms. 17 In the aortic tissues of patients with TAA, here we found that aortic CD248 was significantly increased mainly by the CD8+ T cells (CD248+CD8+) infiltrating the adventitia and media of aortic aneurysms. Interestingly, the recruitment of CD248+CD8+ T cells in situ was coincident with the reduced circulating CD248+CD8+ T cell subpopulation in patients with TAA when compared with patients with CAD and healthy subjects, strongly indicating that CD248 may participate in pathological vascular remodeling via infiltrating CD8+ T cell-involved vascular inflammatory response, particularly in patients with TAA.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Vascular inflammatory reactions seem to play a pivotal role in the development and progression of aortic aneurysms. 17 In the aortic tissues of patients with TAA, here we found that aortic CD248 was significantly increased mainly by the CD8+ T cells (CD248+CD8+) infiltrating the adventitia and media of aortic aneurysms. Interestingly, the recruitment of CD248+CD8+ T cells in situ was coincident with the reduced circulating CD248+CD8+ T cell subpopulation in patients with TAA when compared with patients with CAD and healthy subjects, strongly indicating that CD248 may participate in pathological vascular remodeling via infiltrating CD8+ T cell-involved vascular inflammatory response, particularly in patients with TAA.…”
Section: Discussionmentioning
confidence: 54%
“…Given the previous studies showing that CD248 is closely linked to microvasculature maturation, 17 we reasoned that CD248 is also involved in pathological accumulation of microvessels in the adventitia and media of aortic aneurysms. We next examined the changes of CD248 expression in aortic walls of patients with TAA.…”
Section: Resultsmentioning
confidence: 94%
“…Among innate immune cells in AAA patients, infiltrating NK cells can produce a high level of pro-inflammatory cytokines and perforin that might cause or exacerbate aortic tissue damage and increase the cytotoxicity against aortic SMCs ( 22 ). Dendritic cells are the most potent antigen-presenting cells that come in contact with T cells within lymphoid follicles and have a role in regulating the functional activity of immune response in AAA ( 23 ). Neutrophils appear to be one of the early contributors in AAA formation through secreting some specific ECM-degrading enzymes and neutrophil protease ( 3 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) are a kind of antigen presenting cells (APC) which are able to process and expose antigen components to T lymphocytes, play a key role in the induction of innate immune responses and are implicated in the immune tolerance to self-antigens ( 40 , 41 ). Krishna et al.…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…Krishna et al. indicated that depletion of CD11c + cells can significantly decrease the maximum diameter of AAAs 28 days after angiotensin II infusion ( 40 ), which suggests that DCs may also have important impact on the development of AAA.…”
Section: Innate Immune Cellsmentioning
confidence: 99%